Evaluating peace operations / by Paul F.Diehl and Daniel Druckman - "Diehl, Paul F" (New Delhi, 2011)
Explores the complexities of evaluating peace operation outcomes, providing an original, detailed framework for assessment. The authors address both the theoretical and the policy-relevant aspects of evaluation as they cover the full gamut of mission goals. Numerous examples from specific peace operations illustrate the discussion.|There has been a great deal written on why peace operations succeed or fail.... But how are those judgments reached? By what criteria is success defined? Success for whom? Paul Diehl and Daniel Druckman explore the complexities of evaluating peace operation outcomes, providing an original, detailed framework for assessment. The authors address both the theoretical and the policy-relevant aspects of evaluation as they cover the full gamut of mission goals from conflict mitigation, containment, and settlement to the promotion of democracy and human rights. Numerous examples from specific peace operations illustrate their discussion. A seminal contribution, their work is a foundation not only for the meaningful assessment of peace operations, but also for approaches that can increase the likelihood of successful outcomes.
Keywords: Peacekeeping